The proton-pump inhibitor lansoprazole enhances amyloid beta production. - Nahuai Badiola; Victor Alcalde; Albert Pujol; Lisa-Marie Münter; Gerd Multhaup; Alberto Lleó; Mireia Coma; Montserrat Soler-López; Patrick Aloy (PLoS ONE, 2013)
A key event in the pathogenesis of Alzheimer's disease (AD) is the accumulation of amyloid-β (Aβ) species in the brain, derived from the sequential cleavage of the amyloid precursor protein (APP) by β- and γ-secretases. Based on a systems biology study to repurpose drugs for AD, we explore the effect of lansoprazole, and other proton-pump inhibitors (PPIs), on Aβ production in AD cellular and animal models. We found that lansoprazole enhances Aβ37, Aβ40 and Aβ42 production and lowers Aβ38 levels on amyloid cell models. Interestingly, acute lansoprazole treatment in wild type and AD transgenic mice promoted higher Aβ40 levels in brain, indicating that lansoprazole may also exacerbate Aβ production in vivo. Overall, our data presents for the first time that PPIs can affect amyloid metabolism, both in vitro and in vivo.